STRATEGI PENGEMBANGAN WISATA AGRO DI BANYUWANGI (Jurnal Ilmiah Pariwisata, 2016)
Its majority of Indonesian are farmers who live in countryside region, has a great opportunity to develop agribusiness in rural. To lift the prices of agribusiness products and Because of Banyuwangi closed to Bali, that’s why, Agribusiness in Banyuwangi not only supply the local market but also expand the market to tourism industries in Bali and tourism industries in oversea. Having become the agro tourism, Banyuwangi realize that the farmers want to develop a tourism in agro to make a value added from their agriculture. The development of the tourism in agro is one of the alternative tourism that must be done pro farmers and rural tourism development synergy with sustainable tourism.